2016
DOI: 10.1177/0011128714560810
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Morality as a Mediator of the Association Between Parenting Practices and Violent and Property Offending Among a Sample of Juvenile Delinquents

Abstract: Prior research has consistently shown that parenting practices have a direct impact on the levels of delinquency in children and on the development of their moral beliefs. Several studies have also found support for a link between levels of moral reasoning and offending. Using a sample of juvenile delinquents, this research tested the ability of morality to act as a mediator for the association between parenting practices and delinquency. Results supported the findings of past research in terms of the direct e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 50 publications
(100 reference statements)
2
21
0
4
Order By: Relevance
“…Specifically, both mother’s and father’s ineffective parenting practices predicted lower moral identity and moral values in the structural equation model, which in turn predicted significant increases in the incidence of cyberbullying. This finding is congruent with prior research that has shown that morality can mediate between parenting practices and delinquent behaviors (Ishoy, 2017; Svensson et al, 2013, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, both mother’s and father’s ineffective parenting practices predicted lower moral identity and moral values in the structural equation model, which in turn predicted significant increases in the incidence of cyberbullying. This finding is congruent with prior research that has shown that morality can mediate between parenting practices and delinquent behaviors (Ishoy, 2017; Svensson et al, 2013, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Prior research has found that poor and harsh parenting has been associated with higher levels of moral disengagement (Campaert, Nocentini, & Menesini, 2018;Wang, Wu, & Chong, 2019). High parental monitoring and low parental hostility, on the other hand, reduce the risk of moral disengagement (Ishoy, 2017). In a recent study, Qi (2019) found that harsh parenting was both directly and indirectly related to aggression via moral disengagement.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Family support brings greater resources and better relational networks, making at-risk adolescents better able to cope [19,20], and parents' commitment to their children's education is associated with a high level of prosociality [21]. Positive parentality constitutes a definite deterrent to crime [22] because it is accompanied by support in education and connection with the world of work [23]. Attachment to school is considered a protective factor against criminal behavior because it links the adolescent to an educational setting structured by rules [23][24][25].…”
Section: Introductionmentioning
confidence: 99%